Transparent Electrodes: Highly Conductive PEDOT:PSS Nanofibrils Induced by Solution‐Processed Crystallization (Adv. Mater. 14/2014). (April 2014) - Kim, Nara; Kee, Seyoung; Lee, Seoung Ho; Lee, Byoung Hoon; Kahng, Yung Ho; Jo, Yong‐Ryun; Kim, Bong‐Joong; Lee, Kwanghee
<x xml:space="preserve">Abstract</x> The crystalline nanostructure of intrinsically conducting polymers is formed via an all‐solution process, leading to a highly conducting state. H2SO4 post‐treatment induces a significant structural rearrangement in PEDOT:PSS films, developing crystalline nanofibrils with a stoichiometrically optimal amount of PSS, and this dramatically increases conductivity up to σdc ≈ 4380 S cm−1. The highly conductive PEDOT:PSS exhibits potential as a transparent electrode in printable optoelectronic devices, as described by K. Lee, S. H. Lee, and co‐workers on page 2268. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>